Islamic Art and Architecture; A Critical and Pathologic Review - Jalal Mohaddesi; Hadi Nadimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Relation between Architecture and Religion is a known discourse in Iran. Considering this relation in the context of Islamic Art, City and/or architecture, it is rooted in Oriental and Historic studies inherited among generations of researchers during the past years. The timeline view shows critical points upon which the discourse and its context has been shaped, modified, and developed evolutionarily. These critical points could be brought in four main categories which “corrects”, “transforms”, “methodologically” proposes or even totally “rejects” the background studies and/or established approaches in it. Exploring these critics considering their basics and criteria would help an inducing pathology of the field, among which diverse viewpoints, deductive and/or disciplinary approaches, theoretical ambiguity, inappropriate methodology, etc. could be mentioned. This critical and pathological review may help to analyze and then organize the status quo of the literature although in a passive a priori approach. It seems that an active and a posteriori approach would lead to a better methodology in research. Considering the “Relation” and the multidisciplinary nature of its components as in Art, City, Architecture & Religion (here Islam), an interdisciplinary approach in research is inevitable. The interdisciplinary approach not only hands over criteria for better criticizing the background of the field but also would shed light over the onward march of the research.